Zika Virus Potentiates the Development of Neurological Defects and Microcephaly: Challenges and Control Strategies - Siddique, Rabeea; Liu, Yang; Nabi, Ghulam; Sajjad, Wasim; Xue, Mengzhou; Khan, Suliman (Frontiers in Neurology, 2019)
Since the beginning of the Zika Virus (ZIKV) epidemic, thousands of cases presenting ZIKV symptoms were recorded in Brazil, Colombia (South America), French Polynesia and other countries of Central and North America. In Brazil, during ZIKV outbreak thousands of microcephaly cases occurred that caused a state of urgency among scientists and researchers to confirm the suspected association between ZIKV infection and microcephaly. In this review article we comprehensively studied scientific literature to analyze ZIKV relationship with microcephaly, recent experimental studies, challenge and shortcomings in previously published reports to know about the current status of this association. The evidences supporting the association of ZIKV infection with congenital microcephaly and fetal brain tissue damage is rapidly increasing, and supplying recent information about pathology, clinical medicine, epidemiology, mechanism and experimental studies. However, serious attention is required towards ZIKV vaccine development, standardization of anthropometric techniques, centralization of data, and advance research to clearly understand the mechanism of ZIKV infection causing microcephaly.